2020
DOI: 10.1109/tvcg.2020.3032761
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Work in Augmented Reality: A Survey

Abstract: In Augmented Reality (AR), users perceive virtual content anchored in the real world. It is used in medicine, education, games, navigation, maintenance, product design, and visualization, in both single-user and multi-user scenarios. Multi-user AR has received limited attention from researchers, even though AR has been in development for more than two decades. We present the state of existing work at the intersection of AR and Computer-Supported Collaborative Work (AR-CSCW), by combining a systematic survey ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 164 publications
(380 reference statements)
0
51
0
Order By: Relevance
“…Furthermore, the Microsoft HoloLens may be of great relevance for collaborative AR scenarios (Sereno et al 2020) and remote collaboration scenarios. Previous approaches on sharing live experiences in a certain user's environment are based on real-time scene capture as well as efficient data streaming and VR-based visualisation for remote users (Stotko et al 2019a, b) as required for efficient consulting or maintenance purposes that reduce the need for physical on-site presence of experts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Microsoft HoloLens may be of great relevance for collaborative AR scenarios (Sereno et al 2020) and remote collaboration scenarios. Previous approaches on sharing live experiences in a certain user's environment are based on real-time scene capture as well as efficient data streaming and VR-based visualisation for remote users (Stotko et al 2019a, b) as required for efficient consulting or maintenance purposes that reduce the need for physical on-site presence of experts.…”
Section: Discussionmentioning
confidence: 99%
“…The research topic of collaborative interfaces in AR is strongly related to the world of robotics. A state of the art that highlights the intersections between AR and computer-supported collaborative work and related future research scenarios can be found in [138]. Some of these applications are dedicated to the navigation of architecture, interacting with other users who experience the same simulation [139].…”
Section: Collaborative Interfacesmentioning
confidence: 99%
“…Finally, much of past work on video-conferencing focuses their research measures/outcomes on the feeling of presence or immersion which has been found to be improved with immersive headset experiences (augmented or virtual reality) [28,33] and to positively influence performance [36]. On the one hand, VR/AR headsets could help reduce the number of monitors hardware needed to work from home and therefore help workers save space and configuration time [20].…”
Section: Implication For Hci Researchmentioning
confidence: 99%